IELTS Speaking Training for High School Teachers in Yogyakarta - Subekti, Adaninggar Septi; Susyetina, Arida (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service activity aimed to facilitate teachers at Tumbuh High School Yogyakarta to learn to speak using the International English Language Testing System (IELTS) standard through a ten-meeting training programme. Seven teachers participated in this teacher development training we (the authors) facilitated. The ten meetings consisted of a pre-test, six face-to-face training sessions, a post-test, a facilitator-participant discussion, and a discussion session between the facilitators and the school’s curriculum coordinator regarding the participants’ progress. During the six face-to-face training sessions, the participants familiarised themselves with three parts of IELTS Speaking test in which they had to talk about familiar topics, to respond to questions on social issues written in cards, and to respond to the examiner’s follow-up questions, in Part I, Part II, and Part III, respectively. There was an increase of scores of the post-test compared to the pre-test, suggesting the training was quite a success.